2009
DOI: 10.22495/cocv6i3p9
|View full text |Cite
|
Sign up to set email alerts
|

Executive board members’ remuneration: A longitudinal study

Abstract: Remuneration is considered to be closely connected with financial performance (positively), firm size (positively), the organizational structure (negatively) and corporate governance mechanisms (negatively). Furthermore, a connection of ownership structure and executives’ remuneration has been well established (theoretically and empirically) in the literature (agency theory). The paper examines if these relationships are valid in Greece. Greece hasn’t the characteristics of an Anglo-Saxon country. Overall the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…This means that Tobin's q variable has a positive and insignificant relationship on CEO compensation. This is supported by the research of Darmadi (2011), and Lazarides et al (2008) who found a positive and insignificant relationship between Tobin's q and CEO's compensation. According to Darmadi (2011) and Lazariders et al (2008), this shows that there is no relationship between stock premiums and the level of compensation received by the CEO.…”
Section: Multiple Linear Regression Analysissupporting
confidence: 52%
See 1 more Smart Citation
“…This means that Tobin's q variable has a positive and insignificant relationship on CEO compensation. This is supported by the research of Darmadi (2011), and Lazarides et al (2008) who found a positive and insignificant relationship between Tobin's q and CEO's compensation. According to Darmadi (2011) and Lazariders et al (2008), this shows that there is no relationship between stock premiums and the level of compensation received by the CEO.…”
Section: Multiple Linear Regression Analysissupporting
confidence: 52%
“…This means that the variable return on assets has a significant positive relationship with CEO compensation. This is supported by the study of Jian et al (2015), Cai et al (2011), Jaiswall & Bhattacharyya (2016), Lazarides et al (2008), and Iqbal and Shehzad (2010) stated that return on assets has a significant positive relationship on CEO compensation. Return on Asset reflects how much return is generated on every rupiah invested in assets.…”
Section: Multiple Linear Regression Analysismentioning
confidence: 76%
“…Lazarides et al (2008) conduct a study in Greece, a country without Anglo-Saxon characteristics, and confirm that the level of executive remuneration is positively associated with financial performance and negatively associated with corporate governance mechanisms. Parthasarathy et al (2006) use a more comprehensive dataset of Indian firms and find that CEOs who are promoters or owners receive compensation higher and with a greater incentive component.…”
Section: Agency Theory and Executive Compensation Studies In Emergingmentioning
confidence: 65%
“…(Fels, 2010) claimed the GFC has again brought much attention and scrutiny to CEO remuneration packages and that CEO remuneration was one of the causes of the GFC. In the ongoing debate about executive remuneration, as argued by Lazarides et al (2008) citing (Ruiz-Verdú & Singh, 2014) that critics of current remuneration practices argued that remuneration packages are designed to facilitate rent extraction by managers rather than to provide those managers incentives to maximize shareholder wealth. In this debate attention has been directed to the use of hidden or camouflaged forms of remuneration, which appear to be inconsistent with the maximization of shareholder value (Bebchuk & Jackson, 2005) and (Hermalin & Weisbach, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%